Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

through : (-1,4) and (-4,2)

Sagot :

Answer:

y - 4 = 2/3 (x + 1)

Explanation:

The point-slope equation has the following form:

[tex]y-y_0=m(x-x_0)[/tex]

Where (x0, y0) is a point and m is the slope of the line.

The slope can be calculated as:

[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]

Where (x1, y1) and (x2,y2) are two points in the line.

So, replacing (x1, y1) by (-1, 4) and (x2, y2) by (-4, 2), we get:

[tex]m=\frac{2-4}{-4-(-1)}=\frac{-2}{-4+1}=\frac{-2}{-3}=\frac{2}{3}[/tex]

Then, replacing m by 2/3 and (x0, y0) by (-1, 4), we get that the equation of the line is:

[tex]\begin{gathered} y-4=\frac{2}{3}(x-(-1)) \\ y-4=\frac{2}{3}(x+1) \end{gathered}[/tex]

So, the answer is:

y - 4 = 2/3 (x + 1)